2018
DOI: 10.1111/dom.13284
|View full text |Cite
|
Sign up to set email alerts
|

Amodiaquine improves insulin resistance and lipid metabolism in diabetic model mice

Abstract: Our findings suggest that amodiaquine exerts beneficial effects on glucose and lipid metabolism by concurrent activation of PPARα/γ. Furthermore, amodiaquine acts as an alternative insulin-sensitizing agent with a positive influence on lipid metabolism and has potential to prevent and treat type 2 diabetes while reducing the risk of lipid abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Interestingly, a recent study by Jung et al . [36] reported that amodiaquine, an antimalarial agent, has a potential to concurrently activate PPARα and γ. The authors showed that amodiaquine has a potential to improve insulin resistance and lipid metabolism in diabetic mice model [36].…”
Section: An Update On the New Pparα/γ Dual Agonists Being Exploredmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a recent study by Jung et al . [36] reported that amodiaquine, an antimalarial agent, has a potential to concurrently activate PPARα and γ. The authors showed that amodiaquine has a potential to improve insulin resistance and lipid metabolism in diabetic mice model [36].…”
Section: An Update On the New Pparα/γ Dual Agonists Being Exploredmentioning
confidence: 99%
“…[36] reported that amodiaquine, an antimalarial agent, has a potential to concurrently activate PPARα and γ. The authors showed that amodiaquine has a potential to improve insulin resistance and lipid metabolism in diabetic mice model [36]. Intriguingly, amodiaquine not only ameliorated insulin resistance, hyperlipidemia and fatty liver; but, also decreased the body weight gain in high-fat diet-induced obese and genetically modified obese/diabetic mice [36].…”
Section: An Update On the New Pparα/γ Dual Agonists Being Exploredmentioning
confidence: 99%
“…Normal diet (D12450B; 3.84 kcal/g; 10% kcal from fat consisting of 25 g/kg soybean oil and 20 g/kg lard) and high-fat diet (HFD) (D12492; 5.24 kcal/g; 60% kcal from fat consisting of 25 g/kg soybean oil and 245 g/kg lard) were purchased from Research Diet, New Brunswick, NJ, USA. All mice except those administered the normal diet (ND) received a HFD for 14 weeks to induce hepatic steatosis [29][30] . From the 8th week, the HFD-fed mice were subcutaneously injected with 2 mg/kg CORT (Sigma-Aldrich Corp., St. Louis, MO, USA) once daily for 7 weeks to promote glucocorticoid-induced hepatic steatosis [31][32] .…”
Section: Animal Experimentsmentioning
confidence: 99%
“…Dietary intervention by phytochemicals in the prevention and treatment of metabolic syndrome has been reported in numerous studies. [47][48][49][50][51][52][53] Therefore, this work aims to investigate the health benefit of quercetin for ameliorating hepatic fat accumulation in HFD-induced obese mice. Firstly, HFD mouse models were established to examine the protective effects of quercetin on hepatic steatosis and inflammation.…”
Section: Introductionmentioning
confidence: 99%